Aero-thermal study of the unsteady flow field in a transonic gas turbine with inlet temperature distortions - Martelli, F; Adami, P; Salvadori, S; Chana, K; Castillon, L (2008)
CFD prediction of the unsteady aero-thermal interaction in the HP turbine stage, with inlet temperature non-uniformity, requires appropriate unsteady modelling and a low diffusive numerical scheme coupled with suitable turbulence models. This maybe referred to as high fidelity CFD. A numerical study has been conducted by the University of Florence in collaboration with ONERA to compare capabilities and limitations of their CFD codes for such flows. The test vehicle used for the investigation is a turbine stage of threedimensional design from the QinetiQ turbine facility known as MT1. This stage is a high pressure (HP) transonic stage that has an un-shrouded rotor, configured un-cooled with 32 stators and 60 rotor blades. Two different CFD solvers are compared that use different unsteady treatment of the interaction. A reduced count ratio technique has been used by the University of Florence with its code HybFlow, while a phase lag model has been used by ONERA in their code, elsA. Four different inlet conditions have been simulated and compared with a focus on the experimental values provided by QinetiQ in the frame of TATEF and TATEF2 EU 6th Framework projects. The differences in terms of performance parameters and hot fluid redistribution, as well as the time- and pitch-averaged radial distributions on a plane downstream of the rotor blade, have been underlined. Special attention was given to the predictions of rotor blade unsteady pressure and heat transfer rates. Copyright © 2008 by ASME.